FOLKLORE-MYTHOLOGICAL ASPECT OF LYRIC HERO-ANNOUNCER AND AUTHOR-ANNOUNCER IN COLLECTION OF OLEG OLGICH «VEGI» - Slonovsca, O. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In the article the question is artistic features of poem Oleg Olgich «Gorodoc 32» that the cycle of poems to the «Unknown warrior». With the help of tool of criticism the attempt of interpretation of text and implication of the adopted works is done. The special attention is concentrated on appearance of lyric hero and on the problem of author position.